Vape shop retailers’ perception and behavior of electronic nicotine delivery systems use at the Kuantan District: a preliminary report - Yaacob, Munirah; Muhammad Ali, Suhaila; Abllah, Zurainie (2022)
Background/ Aims: The opening of new vape shops has sprouted tremendously with the growing popularity of electronic nicotine delivery systems (END). Shop retailers become an essential source of information, advice, and influence for consumers on their vaping habits however the research on vape shop retailers is lagging despite the popularity of END. The survey aimed to assess the retailers’ knowledge and behavior of END usage.